Characterization of a Major Cluster of nif, fix, and Associated Genes in a Sugarcane Endophyte, Acetobacter diazotrophicus - Lee, Sunhee (American Society for Microbiology, 2000)
A major 30.5-kb cluster of nif and associated genes of Acetobacter diazotrophicus (syn. Gluconacetobacter diazotrophicus), a nitrogen-fixing endophyte of sugarcane, was sequenced and analyzed. This cluster represents the largest assembly of contiguous nif-fix and associated genes so far characterized in any diazotrophic bacterial species. Northern blots and promoter sequence analysis indicated that the genes are organized into eight transcriptional units. The overall arrangement of genes is most like that of the nif-fix cluster in Azospirillum brasilense, while the individual gene products are more similar to those in species of Rhizobiaceae or in Rhodobacter capsulatus.